The Role of Islamic Religious Education Teachers in Student Character Formation at Muhammadiyah Elementary School 12 Pamulang - Aryah Marzanah; Muazizah; Arief Maqrufianto; Endang Iskandar; Muhammad Dwi Fajri (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to analyze the role of Islamic Religious Education teachers in building student character at Muhammadiyah Elementary School 12 Pamulang through religious values learning, role models, moral habits, and the strengthening of Islamic school culture. Theoretical framework: This study draws on character education theory, social learning theory, and Islamic education theory, emphasizing the importance of role models, social interactions, and religious habituation in building student character. Literature review: This study examines the concept of character education in Islam, the role of teachers as role models (uswah hasanah), school religious culture, and the relationship between the educational environment and student moral formation. The literature shows that student character is formed through the integration of religious values, social habits, and teacher role models in everyday life. Method: This study uses a qualitative case study design. Data were obtained through observation, in-depth interviews, and documentation involving Islamic Religious Education teachers, students, and school officials at Muhammadiyah Elementary School 12, Pamulang. Data analysis was carried out through data reduction, data presentation, and inductive conclusion drawing. Results: The study indicates that Islamic Religious Education teachers play a strategic, multidimensional role in building student character. Character formation is carried out through learning religious values, habituating worship, providing motivation, moral guidance, and exemplary teacher behavior. School religious culture, such as congregational prayer, Qur'an reading, greeting culture, discipline, and socio-religious activities, has been shown to strengthen the internalization of student character values. Research also shows that students tend to imitate teacher behavior, making teachers a major factor in character formation. However, the influence of digital media, the lack of family supervision, and differences in student character pose challenges to the character development process. Implications: This study emphasizes the importance of strengthening the role of Islamic Religious Education teachers through role models, religious practices, and collaboration among schools, families, and the broader social environment in shaping student character. Novelty: The novelty of this study lies in its integrative analysis of the relationships among teacher role models, school religious culture, and Islamic habits in the internalization of student character in Muhammadiyah elementary schools.